Effects of omega-3 fatty acid supplementation on serum Alanine Transferase and Aspartate Transferase levels in middle-aged patients with type 2 diabetes mellitus - Habib, Tamanna Binte; Akhter, Qazi Shamima (Journal of Bangladesh Society of Physiologist, 2021)
Background: People with type2 diabetes mellitus (DM) are at amplified chance of non-alcoholic fatty liver disease. Objective: To observe the effects of omega-3 fatty acid supplementation Alanine Transferase (ALT) and Aspartate Transferase (AST) in middle age patients with type 2 DM. Methods: A prospective interventional study in 2017, recruited 52 type 2 diabetic patients of both sexes aged 40 to 50 years. Among them, 27 patients were given fish oil capsule orally (omega 3 fatty acid 2g/day) for consecutive 12 weeks and 25 patients without supplementation were selected as control also studied after 12 weeks. Serum ALT and AST of all patients were estimated by enzymatic colorimetric method at baseline and after 12 weeks. For statistical analysis, Paired Student’s ‘t’ test and Unpaired Student’s ‘t’ test were performed. Results: In this study ALT and AST significantly decreased in patients supplemented with omega-3 fatty acid after 12 weeks, ALT (alanine aminotransferase) and AST (aspartate transaminase) were decreased in diabetic patients after supplementation with omega- 3 fatty acid in comparison to control group. Conclusion: It can be concluded that omega-3 fatty acid supplementation was effective to reduce ALT and AST levels in diabetic patients and it may be helpful to minimize the risk of fatty liver in type-2 DM. J Bngladesh Soc Physiol 2021;16(1): 39-43